2010
DOI: 10.1002/anie.201000446
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric [3+2] Cycloadditions of Allenoates and Dual Activated Olefins Catalyzed by Simple Bifunctional N‐Acyl Aminophosphines

Abstract: Bifunctional catalyst: Simple bifunctional N‐Acyl aminophosphines such as 1 were developed to catalyze the first asymmetric [3+2] cycloaddition between allenoates and dual activated olefins. The cycloaddition reactions afford multifunctional chiral cyclopentenes with exclusive regioselectivity, and good to excellent enantioselectivity and yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(37 citation statements)
references
References 85 publications
0
36
0
1
Order By: Relevance
“…[10] This work also suggested the importance of the hydrogen-bond-donating amide group of the bifunctional catalysts 13 for the asymmetric induction. For example, with a similar structure, chiral phosphine catalyst 13 e with the most acidic NH function led to an almost racemic product after long reaction time.…”
Section: Chemcatchem Minireviewsmentioning
confidence: 95%
See 1 more Smart Citation
“…[10] This work also suggested the importance of the hydrogen-bond-donating amide group of the bifunctional catalysts 13 for the asymmetric induction. For example, with a similar structure, chiral phosphine catalyst 13 e with the most acidic NH function led to an almost racemic product after long reaction time.…”
Section: Chemcatchem Minireviewsmentioning
confidence: 95%
“…[22] In 2011, Zhao et al successfully extended the applications of their previous developed amino acid derived bifunctional N-acyl aminophosphine catalyst 13 a [10] to an enantioselective [4+2] cycloaddition of tosylaldimines 38 and a-substituted allenoate 39, which provided an efficient asymmetric access to optically active tetrahydropyridines (Scheme 15, up to 96 % ee). [23] Similarly to previously proposed acting models, [8] TS-1 involves formation of a zwitterion between the chiral phosphine and the allenoate 39, which is possibly assisted by a hydrogen bonding interaction and a P-O interaction, [24] and the dienolate might approach the Re face of the imine to minimize the steric repulsion between the phosphonium intermediate generated from the allenoate and the tosyl (Ts) groups of the imine.…”
Section: [4+2] Cycloadditionsmentioning
confidence: 99%
“…More recently, Zhao et al reported the use of N-H-acyl aminophosphine catalyst 212 derived from an -amino acid, for enantioselective allenoates-arylidenemalononitriles and analogues cycloadditions [96]. Although olefins derived from aliphatic aldehydes are not suitable substrates in this particular transformation, a wide range of olefins derived from aromatic aldehydes provided enantioenriched cyclopentenes in high yield, with good to excellent enantioselectivity and exclusive regioselectivity (Scheme 52).…”
Section: Cycloadditions Of Activated Olefinsmentioning
confidence: 97%
“…9 A few years later, Zhao reported an asymmetric [3 + 2] cycloaddition between allenoates and dual-activated olefin, catalyzed by bifunctional N-acyl amino phosphines. 10 Jacobsen devised cyclohexane-based bifunctional phosphines with a thiourea moiety to promote allene−imine annulation. 11 At the very beginning, we set our goal to develop a family of easily derived bifunctional phosphines that are efficient in asymmetric induction for a wide range of phosphine-mediated processes.…”
Section: Bifunctional Phosphines Derived From Amino Acidsmentioning
confidence: 99%
“…15 Similar types of annulations were also reported by Miller, 9 Marinetti, 16 and Zhao. 10 To test the effectiveness of our amino acid-based phosphines, we chose to investigate their catalytic effects in the [3 + 2] cycloaddition of allenes to α-substituted acrylates. 17 The use of elusive substituted acrylate substrates for the construction of challenging functionalized cyclopentenes with a quaternary stereogenic center made it ideal to evaluate our novel phosphine catalysts.…”
Section: [3 + 2] Annulations Of Allenesmentioning
confidence: 99%